Ntam 'reminiscential oath' taboo in Akan - Agyekum, K. (Language in Society, 2004)
Ntam 'reminiscential oath' among the Akan of Ghana is a commissive form that has statutory force. In it, the oath-taker evokes the memory of historical events that are dangerous and unpleasant to mention. The statutory force of the oath is accomplished by the evocation of these memories in the community which shares them. This article reviews the types of ntam oaths, the contexts for their use, and their structure.
Keywords: Akan verbal taboo; Commissives; Face threat; Ntam oath